PERSEPSI MAHASISWA TERHADAP SOLIDARITAS SOSIAL DAN INTEGRASI BANGSA (Survei Kualitatif Pada Mahasiswa FISIP Universitas Lampung) - Hertanto Hertanto; Arizka Warganegara; Handi Mulyaningsih (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2021)
Researches conducted by the Indonesian Institute of Science (LIPI) and the Indonesian National Counter-Terrorism Agency (BNPT) have revealed that students in some of the major universities in Indonesia have become potentially radical. This study aims to: (a) find out students' perceptions on social solidarity; (b) understand the student perceptions on national integration; (c) analyze the potential of being radical among the students. We conducted a qualitative survey to analyze the student’s perception of radicalism, social integration, and national integration. The study results show that: first, the majority of informants have a positive perception toward social solidarity to their fellow citizens in the community who have a different social, cultural, religious, ethnicity and language background. Second, the majority of informants have a very positive perception of national integration. Third, there is no indication of increasing radical behavior among FISIP University of Lampung’s students.